High Level of Legumain Was Correlated With Worse Prognosis and Peritoneal Metastasis in Gastric Cancer Patients - Wang, Yan; Zhang, Shilong; Wang, Haiwei; Cui, Yuehong; Wang, Zhiming; Cheng, Xi; Li, Wei; Hou, Jun; Ji, Yuan; Liu, Tianshu (Frontiers in Oncology, 2020)
Background: Peritoneal metastasis (PM) in gastric cancer (GC) patients has long been recognized as to associated with poor prognosis. Nevertheless, there are few predictive markers of the peritoneal metastasis. The aim of this study was to assess the predictive impact of Legumain (LGMN) expression in gastric cancer patients with PM. Methods: The study included two patient cohorts, the Cancer Genome Atlas cohort (TCGA, n=443) and the Zhongshan Hospital cohort (ZSHC, n=139). The TCGA STAD cohort with clinical data and HiSeqV2 expression data was download from TCGA hub (https://tcga.xenahubs.net). ZSHC cohort included primary tumor tissues of 139 patients who were diagnosed as advanced gastric cancer with or without peritoneal metastasis at the Department of Medical Oncology, Zhongshan Hospital (Shanghai, China) between January 2009 and June 2016. Expression levels of Legumain were assessed by immunohistochemistry and correlated with clinicopathologic parameters including progress-free survival and overall survival. Results: Characteristics of 443 gastric cancer patients were downloaded from TCGA dataset and a total of 139 advanced gastric cancer patients were included in Zhongshan Cohort. The levels of LGMN were up-regulated in GC, especially for diffuse type GC. GC patients with high level of LGMN were at significantly higher risk of death both in TCGA cohort and Zhongshan cohort. GC patients with LGMN high expression were more likely to suffer PM than these with LGMN low expression (71.25% vs. 38.98%, p < 0.001). Diffuse type GC patients tended to have PM compared to those patients with intestinal GC and those with mixed GC in the Zhongshan cohort (p < 0.001). The level of LGMN, combined with Lauren type and gender, was able to better predict PM in GC patients. The focal adhesion, ecm receptor interaction, cell adhesion molecules cams, TGF-β signaling pathway, JAK-STAT signaling pathway, gap junction, etc., were differentially enriched in phenotypes with high LGMN expression. Conclusion: High level of LGMN correlated with worse prognosis and PM in GC patients.